2018
DOI: 10.1038/s41419-018-0328-0
|View full text |Cite
|
Sign up to set email alerts
|

Hemopexin is required for adult neurogenesis in the subventricular zone/olfactory bulb pathway

Abstract: The neural stem cells (NSCs) of the subventricular zone (SVZ) reside within a specialized niche critical for neurogenesis. Hemopexin, a plasma glycoprotein, has been extensively studied as a heme scavenger at the systemic level. However, little is known about its function in the central nervous system, especially in neurogenesis. In the present study, we demonstrate that deletion of hemopexin leads to neurogenic abnormalities in the SVZ/olfactory bulb (OB) pathway. The lateral ventricle is enlarged in hemopexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…The olfactory bulb together with hippocampal dentate gyrus subventricular and the sub-granular zones, represent the three regions in the brain that undergo adult neurogenesis; the process that maintains continuous turnover of bulbar interneurons. Granular and periglomerular neurons of OB are well known to be differentiating and from cell precursors located in the subventricular zone and migrating to OB where it can respond to odor stimulations ( 42 44 ). In this study, Ki67 positive cells, which represent the newly proliferating nerve cells, was observed in the control MOB.…”
Section: Discussionmentioning
confidence: 99%
“…The olfactory bulb together with hippocampal dentate gyrus subventricular and the sub-granular zones, represent the three regions in the brain that undergo adult neurogenesis; the process that maintains continuous turnover of bulbar interneurons. Granular and periglomerular neurons of OB are well known to be differentiating and from cell precursors located in the subventricular zone and migrating to OB where it can respond to odor stimulations ( 42 44 ). In this study, Ki67 positive cells, which represent the newly proliferating nerve cells, was observed in the control MOB.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities develop in the SV2/olfactory bulb pathways of HPX-null mice that impair neuroblast migration in the subventricular zone as well as the rostral migratory stream. Exogenous HPX inhibited apoptosis and promoted the migration and differentiation of cultured neural stem cells [123].…”
Section: Hemopexin Protects the Blood-brain Barriermentioning
confidence: 97%
“…Besides heme-scavenging, other functions of hemopexin include iron homeostasis, antioxidant protection, anti-inflammatory effects, signaling to promote cell survival, and gene expression [42,43]. Recently, hemopexin was demonstrated to promote neural stem-cell migration and differentiation into neurons and oligodendrocytes in vitro [44]. In relation to cancer, hemopexin was reported to be upregulated in pleural effusions of lung-cancer patients and in plasma of pancreatic-cancer patients before resection [45,46], and the fucosylated form of hemopexin was reported as an accurate serum marker for hepatocellular carcinoma [47,48].…”
Section: Plos Onementioning
confidence: 99%